1977
DOI: 10.1029/gl004i011p00517
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism for ultraviolet photolysis of gaseous chlorine nitrate at 302.5 nm

Abstract: The laboratory photolysis of chlorine nitrate (ClONO2) with 302.5 nm ultraviolet light leads to the destruction per quantum of 4 molecules of ClONO2 and the formation of 1 molecule of O2, 2 of Cl2 and 2 of N2O5. These quantum yields are not consistent with the current assumption that the primary photolysis step for ClONO2 in the stratosphere leads to the formation of ClO plus NO2. A consistent mechanism exists in which the photolytic step involves the decomposition of ClONO2 to ClONO + O(³P). The onset of obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
3

Year Published

1979
1979
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 7 publications
0
10
3
Order By: Relevance
“…This result is disturbingly different from that of Smith et al [2] who postulated process (4) to be the major photolytic decomposition pathway. It is also in contradiction with the conclusion presented by Adler-Golden et al [1], These authors interpret their atomic absorption spectroscopy data in the vacuum uv in favor of a predominant 0( 3 P) production with the quantum yield for C1( 2 P) production being less than 4%.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…This result is disturbingly different from that of Smith et al [2] who postulated process (4) to be the major photolytic decomposition pathway. It is also in contradiction with the conclusion presented by Adler-Golden et al [1], These authors interpret their atomic absorption spectroscopy data in the vacuum uv in favor of a predominant 0( 3 P) production with the quantum yield for C1( 2 P) production being less than 4%.…”
Section: Resultscontrasting
confidence: 55%
“…Its publication is prompted by a report [1] containing in essence conclusions which are in agreement with an earlier letter by Smith et al [2] but being at variance with our results [3,4] and those of others [5].…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…The direct study by Marindli and Johnston (8) found that the NO, yield, corrected for a revised calibration factor (1 I), is less than 40%, and NO, and secondary N20, products have been detected in steady state (11) and static cell (5,9) experiments. 26.…”
mentioning
confidence: 99%
“…Early studies on the photochemistry of ClONO 2 using static-cells or flow-tubes and atomic resonance fluorescence reported that channel 1 was the major dissociation pathway [8][9][10][11] based on the observation of O( 3 P) following photolysis, but could not establish whether these products originated from a primary channel or a secondary process. Marinelli and Johnston detected NO 3 by absorption following ClONO 2 photolysis at 248 nm and reported a yield of 0.5 ± 0.3 for channel 1 [12].…”
Section: Introductionmentioning
confidence: 98%